2020
DOI: 10.1109/access.2020.3025714
|View full text |Cite
|
Sign up to set email alerts
|

Application of GWO-SVM Algorithm in Arc Detection of Pantograph

Abstract: High-speed train will produce pantograph arc during the driving process, which is harmful to pantograph-catenary system. In order to reduce pantograph-catenary system damage, a method based on Gray Wolf algorithm to optimize the binary Support Vector Machine classifier to identify pantograph arc is proposed. In this paper, 5 groups of pantograph current experiments under different conditions are carried out, and the current data in the pantograph-catenary system under different conditions are measured. The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…According to literature, Gray Wolf Optimization (GWO) algorithm is the best one that makes balance between exploration or global research and exploitation or local research [ 33 ]. It has also simple structure, fewer parameters and strong and rapid convergence compared to other bio-inspired algorithms like particle swarm optimization (PSO) or genetic algorithm (GA) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to literature, Gray Wolf Optimization (GWO) algorithm is the best one that makes balance between exploration or global research and exploitation or local research [ 33 ]. It has also simple structure, fewer parameters and strong and rapid convergence compared to other bio-inspired algorithms like particle swarm optimization (PSO) or genetic algorithm (GA) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dataset, accessible in [43], is comprised of recordings of 15 subjects (aged [24][25][26][27][28][29][30][31][32][33][34][35] watching video clips and doing public speaking and mental arithmetic tasks. The dataset is recorded with a wrist-based device (including the following sensors: photoplethysmography, accelerometer, electrodermal activity, and body temperature) and a chest-based device (including the following sensors: ECG, accelerometer, electromyogram, respiration, and body temperature).…”
Section: B Description Of Wesad Datasetmentioning
confidence: 99%
“…The results showed that GWO could quickly and accurately identify the pantograph arc. The obtained classification model was more accurate than the commonly used Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) algorithm [ 35 ]. Almomani (2020) proposed a feature selection model for NIDS.…”
Section: Related Workmentioning
confidence: 99%